1954
DOI: 10.1002/j.2333-8504.1954.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Measures as Predictors of Success in Torpedoman's Mates School*

Abstract: The purpose of this study was to develop a measure of learning ability that would predict success in Navy schools teaching mechanical‐motor skills. When combined with scores from the Navy Basic Test Battery, the learning measure was also expected to increase the predictive effectiveness obtainable from the Basic Battery alone.Learning ability was assessed in terms of a cumulative rate‐of‐work score based upon five administrations of the Breech Block Performance Test. A sound film describing the assembly of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1954
1954
1966
1966

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The analysis clearly demonstrates the possibility of predicting a linear function of course grades from the learning measures derived from two simple objective tests. A canonical correlation analysis of Allison's (1954) data also revealed that the learning measures derived from the Breech Block Test alone predicted later success in Torpedoman's Mates School as effectively as many of the tests of Navy Basic Test Battery.…”
Section: Efficiency Of Learning Measures For Predicting Academic Gradesmentioning
confidence: 93%
“…The analysis clearly demonstrates the possibility of predicting a linear function of course grades from the learning measures derived from two simple objective tests. A canonical correlation analysis of Allison's (1954) data also revealed that the learning measures derived from the Breech Block Test alone predicted later success in Torpedoman's Mates School as effectively as many of the tests of Navy Basic Test Battery.…”
Section: Efficiency Of Learning Measures For Predicting Academic Gradesmentioning
confidence: 93%
“…However, the ECL-A scores did have significant negative correlations with the learning scores from the Breech Block Performance Test and indicates that fleet or recruit personnel who had had limited exl 1 perience in a variety of mechanical-motor tasks tended to earn low |: " scores on the learning task. Fcr the fleet subjects, there was also a significant correlation between the ECL-A and ECL-C scores and scores on the Mechanical Aptitude Test-…”
Section: ' •mentioning
confidence: 94%